The political economy of virtue : luxury, patriotism, and the origins of the French Revolution - Shovlin, John (Cornell University Press, 2006)
"Drawing on hundreds of political economic tracts published in France between the 1740s and the early nineteenth century, Shovlin shows how mid-level French elites (magistrates, clerics, lawyers, soldiers, landed gentlemen) sought to balance their interests and values with the need to regenerate a nation that had seemingly entered a period of decline."--Jacket.